Perceived effects of the hidden curriculum of return to entrepreneurship with the mediation of goal orientation - Ahmad KarimiDashtaki; Mohammadbagher Akbarpour Zangalani (مدیریت و چشم انداز آموزش)
Abstract The purpose of this research is the effect of the perception of the hidden curriculum on the tendency to entrepreneurship with the mediation of goal orientation. This research is applicable in terms of purpose, and descriptive-correlative in terms of data collection method. The statistical population of the research includes all the students of Payam Noor University in the center of Khoi in the academic year of 2012-2013, in the number of 2178 people, and the statistical sample size was 327 people through Morgan's table and using stratified random sampling method. The research data collection tools are Taqvai et al., (2013), Middleton and Migli (1997), and Mirza Safi (2009) questionnaires. Data analysis was done using SPSS and AMOS software. The results of the research showed that the perception of the hidden curriculum positively and significantly predicts goal orientation (β=0.61, p<0.001) and entrepreneurship (p < 0.043, β=0.046). Also, goal orientation positively and significantly predicted entrepreneurial orientation (p<0.023, β= 0.062). Therefore, the hypotheses of the research based on the direct effect of the perception of the hidden curriculum on the goal orientation and tendency to entrepreneurship were confirmed. Extended abstract Introduction Today, trying to deal with the challenges facing organizations has led to the formation of the concept of organizational entrepreneurship (Karimi et al, 2019). Entrepreneurship is a management attitude that gives meaning to concepts such as innovation, flexibility and accountability in the shadow of understanding environmental opportunities. Organizational entrepreneurship occurs when an organization relies on the growth and use of new opportunities of internal and external factors of its organization (Darabi et al, 2019). Regarding the importance of entrepreneurship, it is enough that today the great universities of the world have put the education and development of entrepreneurial thinking on their agenda, and the best reason for this is the "Summary of the Global Declaration on University Education" which was issued in October 1998 under the supervision of UNESCO in Paris. It was said that "the development of entrepreneurial skills and initiatives should be among the major concerns of university education" (Khosravipor et al, 2023). The motivational beliefs of the learners are one of the most effective variables of entrepreneurial conversions. Motivational beliefs are a type of personal and social criteria that people refer to perform or avoid an action. Motivational beliefs as a motivational category are of fundamental importance. According to Dai et al, (1998), motivational belief as an internal mediator provides salient mental structures for cognition, emotion, and behavior. These beliefs include a wide range of literature on the subject. Self-efficacy, academic self-efficacy, task value, and goal orientation are among the motivational beliefs, the latter of which is considered in this research. Goal orientation is based on the assumption that human behavior is purposeful and guided by individual goals. Goal orientation refers to a set of behavioral intentions that explain a person's attitude to participate in learning activities. In other words, goal orientation expresses a coherent pattern of a person's beliefs, which causes a person to approach situations in different ways, engage in activities in that field, and finally provide an answer (Ames, 1992). One of the topics that is unfortunately neglected in the research related to entrepreneurial tendencies is the study of the role of students' perceptions of the hidden curricula of academic environments. The hidden curriculum is the learning that students learn during their time in the institution outside of the official curriculum and from the behaviors and attitudes of their professors (Lalezari & Kakamanshadi, 2023). Since perhaps the biggest challenge of Iran's economy right now is the issue of employment, and research shows that schools are the best place to find the source of entrepreneurial problems; in response to this problem of unemployment, the bodies responsible for the planning of educational centers are encouraging them to take steps towards self-employment and entrepreneurship (Heidari, 2023). Theoretical Framework The main issue was whether Payam Noor University students' perceptions of different aspects of the university's hidden curriculum with the mediating influence of goal orientation have an effect on their entrepreneurial tendencies or not. Literature The hidden curriculum The hidden curriculum in the form of methods that are organized in the university environment affects attitudes, feelings, sensitivities, and what learners see in the world and how they communicate with it (Goodarzi & Jamahi, 2018). Tendency to entrepreneurship Tendency to entrepreneurship is a different concept from the concept of entrepreneurship. Entrepreneurship refers to creating a business or a new organization; it emphasizes the content and answers the question of what kind of business we should enter. But entrepreneurial orientation emphasizes the process and explains what we should do in the process (Ermita et al, 2021). Tendency to entrepreneurship is considered as the process of creating entrepreneurial strategy by which the key-decision makers show the organizational goals, maintaining vision, and creating competitive advantage (Bohlouli et al, 2018). Goal orientation Goal orientation in the educational situation expresses the individual's motivation to study, and affects the individual's responses in learning situations. In fact, goal orientation directs academic behavior and is able to explain the relationship between student beliefs about academic success and involvement and persistence in learning tasks (Bahmaei et al, 2023). Salimi et al, (2023) investigated the effect of the hidden curriculum in the citizenship education of elementary school students in Kerman Shah city. The findings of the research showed that the five dimensions of the physical structure of the school, the social atmosphere of the school, the relationships at school, information and communication technology, and the mechanism of encourage and punishment have an effect on the citizenship education of elementary school students in Kerman Shah city. Lalezari & Kakamanshadi (2023) investigated the relationship between the hidden curriculum of information and communication technology and the social intelligence of student teachers. The results of the study showed that there is a positive and significant relationship between the predictive variable of hidden curriculum of information and communication technology with the variable of social intelligence criterion. Also, the results of statistical analysis showed that among the three components of social intelligence, only the component of social information processing has a significant relationship with this curriculum.